2021
DOI: 10.3389/fimmu.2020.572999
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR4 in Persistent Leptospira interrogans Infection: A Comparative In Vivo Study in Mice

Abstract: Toll-Like Receptor (TLR) 4, the LPS receptor, plays a central role in the control of leptospirosis and absence of TLR4 results in lethal infection in mice. Because human TLR4 does not sense the atypical leptospiral-LPS, we hypothesized that TLR4/MD-2 humanized transgenic mice (huTLR4) may be more susceptible to leptospirosis than wild-type mice, and thus may constitute a model of acute human leptospirosis. We infected huTLR4 mice, which express human TLR4 but not murine TLR4, with a high dose of L. interrogans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(50 reference statements)
0
9
0
1
Order By: Relevance
“…In fact, our data show that serogroup Grippotyphosa and Bratislava-derived LPS seem to be less potent human TLR4 activators compared to serogroup Canicola and Icterohaemorrhagiae ( Figures 4B, D ) , suggesting that human TLR4-activating capabilities by leptospiral LPS might be serovar dependent. In addition, it was recently reported that the inflammatory response to an infection with L. interrogans serovar Copenhageni strain Firocruz L1-130 in humanized TLR4/MD2 transgenic mice was comparable to the response of congenic wild-type mice expressing mouse TLR4, suggesting that functional human or mouse TLR4 is required to control infection by this strain ( 50 ). Alternatively, the differences between our observations and previously published results could also be explained by differences in the LPS purification method.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our data show that serogroup Grippotyphosa and Bratislava-derived LPS seem to be less potent human TLR4 activators compared to serogroup Canicola and Icterohaemorrhagiae ( Figures 4B, D ) , suggesting that human TLR4-activating capabilities by leptospiral LPS might be serovar dependent. In addition, it was recently reported that the inflammatory response to an infection with L. interrogans serovar Copenhageni strain Firocruz L1-130 in humanized TLR4/MD2 transgenic mice was comparable to the response of congenic wild-type mice expressing mouse TLR4, suggesting that functional human or mouse TLR4 is required to control infection by this strain ( 50 ). Alternatively, the differences between our observations and previously published results could also be explained by differences in the LPS purification method.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study using humanized TLR4 mice [100], which are immune competent mice, showed that those mice are not more sensitive to acute leptospirosis, but rather suggested that a functional TLR4 receptor being of mouse or human was required to protect the mice against leptospirosis. Whether the immunoglobulin response would have been different has not been investigated since only the first 15 days post-infection have been studied [101].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…However, mouse strains that express an impaired TLR4 in their immune cells (C3H-HeJ) are susceptible to lethal and sublethal leptospirosis ( Pereira et al., 1998 ; Nally et al., 2005 ; Viriyakosol et al., 2006 ; Richer et al., 2015 ) and those that have been engineered to not express TLR4 (C57BL/6J-TLR4 ko ) succumb to infection ( Chassin et al., 2009 ). We found recently that rather than leptospiral-LPS sensing, the presence of a fully functional TLR4 receptor in mice is necessary to control acute leptospirosis ( Nair et al., 2021 ). In this study, we used the C3H-HeJ mouse model, which recapitulates susceptibility to leptospirosis, to analyze differences in cell-mediated immune markers engaged by pathogenic disseminators as well as those engaged by saprophytic non-disseminators during the earliest phase of infection with Leptospira, at 24h and 72h.…”
Section: Introductionmentioning
confidence: 99%